Predicting diabetic foot ulcer infection using the neutrophil-to-lymphocyte ratio: a prospective study. (2nd September 2019) - Altay, Fatma Aybala; Kuzi, Semanur; Altay, Mustafa; Ateş, İhsan; Gürbüz, Yunus; Tütüncü, Emin Ediz; Şentürk, Gönül Çiçek; Altın, Nilgün; Şencan, İrfan
Abstract : Objective: To investigate whether the neutrophil-to-lymphocyte ratio (NLR) may be used in the early stage risk assessment and follow-up in diabetic foot infection Methods: Over a five-year study, NLR values on admission and day 14 of treatment were matched with their laboratory and clinical data in a cohort study. Patients were followed-up or consulted in several clinics or polyclinics (infectious diseases). Results: Admission time NLR was higher, in severe cases as indicated by both Wagner and PEDIS infection scores (severe versus mild Wagner score NLR 6.7 versus 4.2; p=0.04; for PEDIS score NLR 6.3 versus 3.6; p=0.03, respectively). In patients who underwent vascular intervention (12.6 versus 4.6; p=0.02); amputation indicated (9.2 versus 4.1; p=0.005) and healed afterwards (6.9 versus 4.3; p<0, 001), when matched with others. NLR was also found to be correlated with duration of both IV antibiotic treatment (r=0.374; p=0.005) and hospitalisation (r=0.337; p=0.02). Day 14 NLR was higher in patients who underwent vascular intervention (5.1 versus 2.9; p=0.007) when matched to others. Conclusion: Patients with higher NLR values at admission had more severe diabetic foot infection, higher risk for amputation, need for long-term hospitalisation and aggressive treatment. However, they also have more chance of benefit from treatment.